Improving the sexual health of young people experiencing homelessness. (2nd November 2021) - McGregor, Fiona; Paisi, Martha; Robinson, Ann; Shawe, Jill
Abstract : The sexual health needs of young people experiencing homelessness in the UK have not been researched adequately. This study aimed to examine knowledge and attitudes around sexual health and contraceptive use amongst this vulnerable group to develop suitable models of care in the community. A qualitative ethnographic case-study following Burawoy's extended case method was used. Semi-structured interviews with 29 young people experiencing homelessness and five key workers in London hostels were carried out together with ethnographic observations and analysis of documentary evidence. Thematic analysis was undertaken. Demographic data were collected. Three significant themes were identified: risks and extreme vulnerability, relationships and communication difficulties and emergence of a culture of homelessness. Young people experiencing homelessness require specialist delivery of sexual health care in safe surroundings. Initial care should focus on assessment of basic needs and current state of being. Establishing trusting relationships and considering ongoing vulnerability, can help promote meaningful and personalised sexual healthcare both at policy and practice level.